ANALISIS MANAJEMEN PEMASARAN USAHA PADA TOKO ELEKTRONIK UFO DI PALANGKA RAYA - Sriafni Y Siburian; Pebrita Simbolon; Purada Lumban Raja (STKIP Persada Khatulistiwa Sintang, 2026)
This study examines the marketing management practices of UFO Electronics Store in Palangka Raya, a local retail business that continues to adapt to rapid changes in consumer behavior and competitive pressure from digital marketplaces. The research aims to describe how the store maintains customer loyalty, identifies its strengths and weaknesses in marketing, and evaluates the effectiveness of its current strategies. A qualitative descriptive method was employed, using in-depth interviews with the store’s promoter and direct observations of operational activities to obtain a comprehensive understanding of real conditions. The results show that interpersonal service plays a central role in shaping customer trust and satisfaction, making it the store’s main competitive advantage. However, digital marketing efforts remain limited and administrative processes are still conducted manually, reducing efficiency and responsiveness. The study recommends strengthening digital marketing integration, improving administrative systems, and maintaining personal service quality as a unique value that differentiates the store from online competitors. These improvements can help the store enhance competitiveness and expand its market reach.